Social Engineering as a Major Cybersecurity Threat: Analysis of Challenges and Solutions for Organizations - Budi Wibowo (International Journal of Science Education and Cultural Studies, 2024)
Social engineering is a psychological manipulation technique used by attackers to exploit human weaknesses in information security. This research aims to identify the challenges organizations face in protecting themselves from social engineering attacks and offer effective solutions. Through analysis of case studies and relevant literature, it was found that a lack of employee awareness and training is one of the main causes of the success of these attacks. In addition, many organizations still rely on inadequate technology to detect threats. To address these issues, this paper recommends implementing regular training programs, strengthening security policies, and using advanced technology. With this comprehensive approach, organizations can strengthen their defences and reduce the risks associated with social engineering. Organizations should prioritize continuous education programs, foster a culture cantered on security, and establish protocols that encourage alertness. Moreover, robust access controls, defined incident reporting processes, and the use of technology like behavioural analytics can further reduce the risks posed by social engineering.